1998
DOI: 10.1021/jf9800920
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Class-Specific Competitive ELISA for the Benzoylphenylurea Insecticides

Abstract: A competitive enzyme-linked immunosorbert assay (ELISA) was developed for the quantitative detection of five benzophenylurea insecticides in soil (90% methanol extraction) and water. No significant matrix effects were observed. Conjugates of diflubenzuron derivatives with proteins were prepared by attachment at either the urea nitrogen of diflubenzuron or the 4-position of the aniline ring, wherein bridging groups of various lengths were used between the hapten and the protein carrier. All combinations of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 27 publications
2
57
0
1
Order By: Relevance
“…It is well established that immunoassays for small molecules using different but analogous haptens and alternative conjugation strategies can improve the assay performance in sensitivity and/or speci®city. 29,30 Thomson and Sporns 31 improved the detection limits of an assay for STZ by optimising the hapten/protein ratios and enzyme substrates used in the assay. In the study reported here, the number of drugs that could be measured by R451 increased when using a heterologous coating conjugate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that immunoassays for small molecules using different but analogous haptens and alternative conjugation strategies can improve the assay performance in sensitivity and/or speci®city. 29,30 Thomson and Sporns 31 improved the detection limits of an assay for STZ by optimising the hapten/protein ratios and enzyme substrates used in the assay. In the study reported here, the number of drugs that could be measured by R451 increased when using a heterologous coating conjugate.…”
Section: Resultsmentioning
confidence: 99%
“…The need to consider both the structure of the hapten as well as competitors and linkers is obvious from the considerable amounts of literature available. 22,29,30,34,35 In all cases, assay speci®city and/or sensitivity have been manipulated by careful hapten design. Selection of the location of linkage to carrier molecules is vital, since it is often necessary to avoid using functional groups that form the character of the molecule, hence selection of the R-group for linkage in this case.…”
Section: Resultsmentioning
confidence: 99%
“…Abs were produced in rabbits as described by Wang et al [29]. Female New Zealand white rabbits were immunized by intradermal and intramuscular injections of CAP haptens conjugated to KLH.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Many immunoassays used for detection of low molecular weight food contaminants such as an algaecide [30], antibiotics [6,16,[31][32][33][34][35], cork taint [36], herbicides [37][38][39][40], mycotoxins [41,42], pesticides [43][44][45][46][47][48], veterinary drugs [49][50][51] and other chemicals [52][53][54][55][56] have been developed with the use of CAMM methods (Table 1). CAMM can be used to assist in hapten design, study antibody-antigen recognition in cross-reactivity studies and model antibody binding sites (Table 1).…”
Section: Introductionmentioning
confidence: 99%